Measurements of top-quark pair differential cross-sections in the e mu channel in pp collisions at root s=13 TeV using the ATLAS detector - Çetin, Serkant Ali (SPRINGER, 2017)
This article presents measurements of t (t) over bar differential cross-sections in a fiducial phase-space region, using an integrated luminosity of 3.2 fb(-1) of proton-proton data at a centre-of-mass energy of root s = 13 TeV recorded by the ATLAS experiment at the LHC in 2015. Differential crosssections are measured as a function of the transverse momentum and absolute rapidity of the top quark, and of the transverse momentum, absolute rapidity and invariant mass of the t (t) over bar system. The t (t) over bar events are selected by requiring one electron and onemuonof opposite electric charge, and at least two jets, one of which must be tagged as containing a b-hadron. The measured differential cross-sections are compared to predictions of next-to-leading order generators matched to parton showers and the measurements are found to be consistent with all models within the experimental uncertainties with the exception of the Powheg-Box + Herwig++ predictions, which differ significantly from the data in both the transverse momentum of the top quark and the mass of the t (t) over bar system.